THE INFLUENCE OF ANTI STRESS MASSAGE IN WELLNESS AND MUSCLE RELAXATION IN BELLY DANCE FOR PRACTITIONERS (Fiep Bulletin - online, 2016)
As the largest organ in the human body skin and the first contact with the environment, the touch becomes more effective communication than speech. Massage in turn, is a resource that promotes pain relief and injury (FRITZ, 2000) and as body image change method. (Lederman, 2001) Objective: To verify the benefits of anti-stress massage on postural education, welfare and muscle relaxation in belly dance practitioners. Method: Study field research, interventional, qualitative conducted with 12 women aged between 18-50 years. There were 5 anti-stress massage sessions on the back and to evaluate the results we used the goniometer of Carci mark, Apley test, 3rd finger-soil, Stibor Index, Schober Score and questionnaires: Pain analysis (EVA), Stress Scale Standard and humor. Conclusion: Through this experimental research, we concluded that the anti-stress massage was effective in decreasing the stress, increase flexibility immediate, self esteem and reduction of high DOMS. Showed significant results in the improvement of 8% of shoulder flexion, extension 7% to 6% and abduction; 11% at the lumbar spine in flexion and extension 7% and 6% for cervical flexion. But for deeper results, indicate long-term research on the benefits anti-stress massage.
Keywords: Wellbeing; Belly Dancing; anti-stress massage.